FUNGSI BAGIAN HUKUM SEKRETARIAT DAERAH DALAM PENYUSUNAN PRODUK HUKUM KABUPATEN PONOROGO - Ferry Irawan Febriansyah; Sudi Rahayu (Legal Standing : Jurnal Ilmu Hukum, 2022)
Preparation of regional regulations is the main task in the legal department. Where there are 3 sub-coordinators in the legal department, namely the sub-coordinator of legislation, sub-coordinator of legal aid and sub-coordinator of documentation and information. Here the author will focus more on the sub-coordinator of legislation because it relates to the preparation of existing legal products in Ponorogo Regency. In this study, the author uses an empirical juridical research method, namely using an approach by paying attention to how a law that exists in the Act is implemented directly in the community. The author compares the preparation of a regional law that has been implemented by the legal department with existing laws and regulations. The author in his research uses the type of field research (field research) where researchers directly come to the Legal Section of the Ponorogo Regency Regional Secretariat for the process of collecting data and interviews. With the completion of this research, it is expected to provide an overview to the public how the process of drafting legal products in Ponorogo Regency, provide additional references to the preparation of regional legal products and provide additional evaluation materials to improve the performance and role of the Legal Department on quality indicators of regional legal products, especially in Ponorogo Regency.